Rancang Bangun Aplikasi Tours and Travel Berbasis Web - ., Andriansah; - UBSI, Iin Fadillah (SPEED - Sentra Penelitian Engineering dan Edukasi, 2021)
Abstract - Tourism has become a source of foreign exchange that has been greatly supported by the government recently. Tourist attractions are starting to clean up and even appear and offer uniqueness. A common problem that occurs is the absence of qualified information media in providing tourism information and travel costs. The tourists certainly have difficulty getting information so it is unfortunate that many tourist attractions are unknown. Another thing that becomes a problem is that the accommodation provided at these tourist attractions is still lacking. Web-based applications can provide solutions in terms of disseminating tourist information and accommodation. By using observational data collection methods and literature study and prototype model software development methods, it becomes a solution to increase regional tourism.Keywords: Application, Information, Tourism Abstraksi –  Pariwisata menjadi salah satu sumber devisa negara yang belakangan sangat di dukung pemerintah. Tempat wisata mulai berbenah bahkan bermunculan serta menawarkan keunikan. Permasalahan umum yang terjadi adalah, tidak adanya media informasi yang mumpuni dalam memberikan informasi wisata serta biaya wisata. Para wisatawan tentunya kesulitan mendapatkan informasi sehingga sangat disayangkan banyak tempat wisata yang tidak diketahui. Hal lain yang jadi permasalahan adalah akomodasi yang disediakan ditempat wisata tersebut yang masih sangat kurang. Aplikasi berbasis web dapat memberikan solusi dalam hal penyebaran informasi wisata serta akomodasi. Dengan menggunakan metode pengumpulan data observasi dan studi pustaka serta metode pengembangan perangkat lunak model prototipe, maka menjadi sebuah solusi untuk meningkatkan wisata daerah.Kata kunci:  Aplikasi, Informasi, Wisata